Frequency of Oral Candidiasis in Type 2 Diabetics - Nomaira Hassan, Muhammad Khurram, Hamama Tul Bushra (Journal of Rawalpindi Medical College, 2013)
Background: To find out the frequency of oral candidiasis in type 2 diabetes mellitus (DM) patients and correlate it with age, gender, duration of diabetic illness, and type of therapy. Methods: In this cross sectional study, 266 type 2 DM patients were inducted. Oral cavity of all patients was examined for oral candidiasis and buccal mucosa scrapings were analyzed by Grams stain to look for fungal hyphae. Results: Sixty eight (25.6%) patients had oral candidiasis. Mean age of patients with and without oral candidiasis was 59.04±5.67 and 54.67±5.62 years(p value <0.05). 57.35% patients with, and 56.56% patients without oral candidiasis were male (p value >0.05). In 23.7% patients, who were on oral hypoglycemic, 28.2% had oral candidiasis, whereas 28.2% on insulin had oral candidiasis (p value >0.05). Patients with 15-20 years of duration of DM had highest incidence (56%) of oral candidiasis. Conclusion: Presence of oral candidiasis significantly correlates with higher patient age group, and longer duration of diabetic illness.